ScVO4 under non-hydrostatic compression: a new metastable polymorph. (12th December 2016) - Garg, Alka B; Errandonea, D; Rodríguez-Hernández, P; Muñoz, A
Abstract: The high-pressure (HP) behaviour of scandium vanadate (ScVO4 ) is investigated under non-hydrostatic compression. The compound is studied by means of synchrotron-based powder x-ray diffraction (XRD) and optical-absorption techniques. The occurrence of a non-reversible phase transition is detected. The transition is from the zircon structure to the fergusonite-type structure and takes place around 6 GPa with nearly 10% volume discontinuity. XRD measurements on the pressure cycled sample confirm for the first time that the fergusonite-type ScVO4 can be recovered as the metastable phase at ambient conditions. Raman spectroscopic measurements verify the metastable phase to be of a fergusonite-type phase. Theoretical calculations also corroborate the experimental findings. The fergusonite phase is found to be stiffer than the ambient-pressure zircon phase, as indicated by the observed experimental and theoretical bulk moduli. The optical properties and lattice-dynamics calculation of the fergusonite ScVO4 are discussed. At ambient pressure the band gap of the zircon (fergusonite)-type ScVO4 is 2.75 eV (2.3 eV). This fact suggests that the novel metastable polymorph of ScVO4 can have applications in green technologies; for instance, it can be used as photocatalytic material for hydrogen production by water splitting.